Walking the Plank: An Experimental Paradigm to Investigate Safety Voice - Noort, Mark C.; Reader, Tom W.; Gillespie, Alex (Frontiers in Psychology, 2019)
The investigation of people raising or withholding safety concerns, termed safety voice, has relied on report-based methodologies, with few experiments. Generalisable findings have been limited because: the behavioural nature of safety voice is rarely operationalised; the reliance on memory and recall has well-established biases; and determining causality requires experimentation. Across three studies, we introduce, evaluate and make available the first experimental paradigm for studying safety voice: the ‘Walking the plank’ paradigm. This paradigm presents participants with an apparent hazard (walking across a weak wooden plank) to elicit safety voice behaviours, and it addresses the methodological shortfalls of report-based methodologies. Study 1 (n = 129) demonstrated that the paradigm can elicit observable safety voice behaviours in a safe, controlled and randomised laboratory environment. Study 2 (n = 69) indicated it is possible to elicit safety silence for a single hazard when safety concerns are assessed and alternative ways to address the hazard are absent. Study 3 (n = 75) revealed that manipulating risk perceptions results in changes to safety voice behaviours. We propose a distinction between two independent dimensions (concerned-unconcerned and voice-silence) which yields a 2x2 safety voice typology. Demonstrating the need for experimental investigations of safety voice, the results found a consistent mismatch between self-reported and observed safety voice. The discussion examines insights on conceptualising and operationalising safety voice behaviours in relationship to safety concerns, and suggests new areas for research: replicating empirical studies, understanding the behavioural nature of safety voice, clarifying the personal relevance of physical harm, and integrating safety voice with other harm-prevention behaviours. Our article adds to the conceptual strength of the safety voice literature and provides a methodology and typology for experimentally examining people raising safety concerns.